Queens of Fennbirn - Blake, Kendare (Blake, Kendare. Three dark crowns, 2018)
"The Young Queens" is the story of a set of triplet sisters destined to fight to the death to win the crown; "The Oracle Queen" tells the story of the last queen born with the gift of sight.